Doing Evolution in Economic Geography. (2nd April 2016) - Pike, Andy; MacKinnon, Danny; Cumbers, Andrew; Dawley, Stuart; McMaster, Robert
Abstract: Evolutionary approaches in economic geography face questions about the relationships between their concepts, theories, methods, politics, and policy implications. Amidst the growing but unsettled consensus that evolutionary approaches should employ plural methodologies, the aims here are, first, to identify some of the difficult issues confronting those working with different frameworks. The concerns comprise specifying and connecting research objects, subjects, and levels; handling agency and context; engaging and integrating the quantitative and the qualitative; comparing cases; and, considering politics, policy, and praxis. Second, the purpose is to articulate a distinctive geographical political economy approach, methods, and illustrative examples in addressing these issues. Bringing different views of evolution in economic geography into dialogue and disagreement renders methodological pluralism a means toward improved understanding and explanation rather than an end in itself. Confronting such thorny matters needs to be embedded in our research practices and supported by greater openness; more and better substantiation of our conceptual, theoretical, and empirical claims; enhanced critical reflection; and deeper engagement with politics, policy, and praxis.